A one-way text messaging intervention for obesity. (April 2016) - Ahn, Ahleum; Choi, Jaekyung
Introduction: Worldwide, there has been a startling increase in the number of people who are obese or overweight. Obesity increases the risk of cardiovascular disease and overall mortality. Mobile phone messaging is an important means of human communication globally. Because the mobile phone can be used anywhere at any time, mobile phone messaging has the potential to manage obesity. We investigated the effectiveness of a one-way text messaging intervention for obesity. Methods: Participants' body mass index and waist circumference were measured at the beginning of the programme and again after 12 weeks. The text message group received text messages about exercise, dietary intake, and general information about obesity three times a week, while the control group did not receive any text messages from the study. Results: Of the 80 participants, 25 subjects in the text message group and 29 participants in the control group completed the study. After adjusting for baseline body mass index, the body mass index was significantly lower in the text message group than in the control group (27.9 vs 28.3; p = 0.02). After adjusting for the baseline waist circumference, the difference of waist circumference between the text message group and control group was not significant (93.4 vs 94.6; p = 0.13). Discussion: The one-way text messaging intervention was a simple and effective way to manage obesity. The one-way text messaging intervention may be a useful method for lifestyle modification in obese subjects.